Anti-MDA5 antibody-positive dermatomyositis with rapidly progressive interstitial lung disease: report of two cases. Issue 4 (28th April 2021) - Mehta, Asmita A; Paul, Tisa; CB, Mithun; Haridas, Nithya
Abstract : Melanoma differentiation-associated protein 5 (MDA5) antibody-positive dermatomyositis (DM) displays unique cutaneous and pathologic features. We describe two cases of myositis-associated rapidly progressive interstitial lung disease (RP-ILD). The patients were two women from Kerala, India. Both patients had anti-MDA5 antibody-positive myositis. Both patients presented with RP-ILD without any clinical features of myositis and succumbed to their illness despite aggressive medical treatment. Anti-MDA5-antibody-positive DM is characterised by amyopathic disease with rapidly progressive and fatal ILD.